Phenocam - Red Chromatic Coordinates (RCC) Composite Image Mean Values from Röbäcksdalen Research Area, Mast 10m Phenocam 01 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2022)
Red Chromatic Index (RCI) also known as Red Chromatic Coordinate (RCC) is a measure of the redness of vegetation. It is calculated from daily averaged RGB (Red, Green, Blue) composites values of digital images captured by PhenoCams.
Röbäcksdalen Field Research Station (2022). Phenocam - Red Chromatic Coordinates (RCC) Composite Image Mean Values from Röbäcksdalen Research Area, Mast 10m Phenocam 01, 2020-03-27–2020-10-04 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/VwYL-9fV0SaMMamd2qlJoVrb
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap